The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1159/000209273
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Psychological Stress on Female Vocal Quality

Abstract: Psychological stress can influence vocal quality. The purpose of the present study was to determine the effect of stress on female vocal quality. In this experimental study 54 female voices were studied in a stress-inducing and a relaxed condition. In the stress-inducing condition the subjects were asked to read a passage while instructions were used to evoke stress. In the relaxed condition the same reading task but without specific instructions was used. Identical subjective and objective assessment techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 32 publications
3
26
1
2
Order By: Relevance
“…Some of the voice changes, specifically lower pitch, that have been observed by others under experimental conditions of induced stress [20] are similar to those that we observed; it is conceivable, given the nature of the information to be discussed, that some of the health providers experienced a stress reaction that affected their nonverbal characteristics. No monitoring of provider's stress parameters was done for this study.…”
Section: Discussionsupporting
confidence: 87%
“…Some of the voice changes, specifically lower pitch, that have been observed by others under experimental conditions of induced stress [20] are similar to those that we observed; it is conceivable, given the nature of the information to be discussed, that some of the health providers experienced a stress reaction that affected their nonverbal characteristics. No monitoring of provider's stress parameters was done for this study.…”
Section: Discussionsupporting
confidence: 87%
“…Studies investigating acute stress have shown both acoustic and perceptual effects of stress on the voice (Giddens, Barron, Byrd-Craven, Clark, & Winter, 2013;Mendoza & Carballo 1998;Mendoza & Carballo 1999;Schneider et al, 2006;Van Lierde, Van Heule, De Ley, Mertens & Claeys, 2009). The results vary and the individual differences of acoustic changes in the voice due to acute stress seem to be large.…”
Section: Stress and Vocal Symptomsmentioning
confidence: 99%
“…Indeed, an increase in voice pitch is the longest and most commonly reported finding in previous studies examining speech under stress (reviewed in Giddens et al, 2013;Kirchhübel et al, 2011). However, many studies have failed to replicate this finding (e.g., Dietrich and Abbott, 2012;Hecker et al, 1968;Johannes et al, 2000;Streeter et al, 1983;Tolkmitt and Scherer, 1986;Van Lierde et al, 2009). Others report an increase in minimum voice pitch or a decrease in its standard deviation (F0 sd), with no systematic change in mean pitch (Park et al, 2011;Tolkmitt and Scherer, 1986).…”
Section: Introductionmentioning
confidence: 96%